2009
DOI: 10.1002/mame.200800330
|View full text |Cite
|
Sign up to set email alerts
|

Thermal‐ and Sun‐Promoted Generation of Silver Nanoparticles Embedded into Poly(vinyl alcohol) Films

Abstract: Nanocomposites based on poly(vinyl alcohol) and silver nanoparticles were efficiently prepared by sun- and thermal-promoted reduction processes. Uniaxial drawing of the Ag/PVA nanocomposites favoured the anisotropic distribution of silver particles, providing oriented films with polarisation-dependent tunable optical properties. These dichroic properties were more pronounced for nanocomposites produced by sun exposition, which provided more compact and interacting metal clusters. The results obtained suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Closer investigations of the copolymer with 27% mol/mol ethylene revealed that the larger particles were located preferentially in the surface region of the materials and vice versa the smaller ones in the interior . In the case of silver, IR spectra implied that poly(vinyl alcohol) was the reduction agent for silver(I) since a band in the region of C=O stretching vibrations emerged upon irradiation, which was attributed to oxidation of the polymer . Upon drawing of films with gold or silver particles a pronounced dichroism developed, and the visible absorption spectra (polarized light) showed the characteristics described above for samples with polyethylene matrices.…”
Section: Synthetic Polymers As Matrixmentioning
confidence: 89%
See 3 more Smart Citations
“…Closer investigations of the copolymer with 27% mol/mol ethylene revealed that the larger particles were located preferentially in the surface region of the materials and vice versa the smaller ones in the interior . In the case of silver, IR spectra implied that poly(vinyl alcohol) was the reduction agent for silver(I) since a band in the region of C=O stretching vibrations emerged upon irradiation, which was attributed to oxidation of the polymer . Upon drawing of films with gold or silver particles a pronounced dichroism developed, and the visible absorption spectra (polarized light) showed the characteristics described above for samples with polyethylene matrices.…”
Section: Synthetic Polymers As Matrixmentioning
confidence: 89%
“…Tetrachloroaurate(III) and silver(I) was also reduced directly in solid matrices by irradiation with UV light, yielding metal particles of average diameter of the order of 5–25 nm. The diameter of the gold particles decreased considerably with increasing irradiation time . Poly(vinyl alcohol) and poly(ethylene‐ co ‐vinyl alcohol) films (ethylene content 27% mol/mol and 44% mol/mol, respectively) of the order of 70 μm thickness were employed as matrix.…”
Section: Synthetic Polymers As Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the existence of well-defined isosbestic points (at 333 and 650 nm) effectively confirm the existence of at least two different populations of absorbing silver nanostructures. 43 The infrared spectra, Figure stretching as function of blend composition is the most frequently employed method to quantify the relative fraction of "free" and "complexed" C O sites within the PVP chain. [45][46][47] Therefore, the characteristic peak at 1660 cm −1 can be investigated to explore the interaction between PVP and PEG.…”
Section: Resultsmentioning
confidence: 99%